Diabetes and Coronary Heart Disease: A Risk Factor for the Global Epidemic - Maguy Chiha; Mario Njeim; Edgar G. Chedrawy (International Journal of Hypertension)
Cardiovascular disease remains a leading cause of death in the United States and the world. In this we will paper focus on type 2 diabetes mellitus as a risk factor for coronary heart disease, review the mechanisms of atherogenesis in diabetics, the impact of hypertension and the treatment goals in diabetics, the guidelines for screening, and review the epidemiologic consequences of diabetes and heart disease on a global scale. The underlying premise to consider diabetes a cardiovascular disease equivalent will be explored as well as the recommendations for screening and cardiac testing for asymptomatic diabetic patients.